Investigation of the Law of Airflow on a Longwall Face - Daniel J. Brunner; Malcolm J. McPherson (Society for Mining, Metallurgy & Exploration, 1987)
This paper describes an experiment conducted to investigate the law of airflow on a mechanized longwall coal face. Background to the Square Law relating frictional pressure drop and airflow is presented and deviations from this Law are discussed. The procedures used to investigate the Law of Airflow for the longwall are described and the results are presented. The results verify the Square Law relationship for airflow along a mechanized longwall face.